A New High Throughput Screening Platform for Cell Encapsulation in Alginate Hydrogel Shows Improved Hepatocyte Functions by Mesenchymal Stromal Cells Co-encapsulation - Iansante, Valeria; Dhawan, Anil; Masmoudi, Fatma; Lee, Charlotte A.; Fernandez-Dacosta, Raquel; Walker, Simon; Fitzpatrick, Emer; Mitry, Ragai R.; Filippi, Céline (Frontiers in Medicine, 2018)
Hepatocyte transplantation has emerged as an alternative to liver transplant for liver disease. Hepatocytes encapsulated in alginate microbeads have been proposed for the treatment of acute liver failure, as they are able to provide hepatic functions while the liver regenerates. Furthermore, they do not require immunosuppression, as the alginate protects the hepatocytes from the recipient’s immune cells. Mesenchymal stromal cells are very attractive candidates for regenerative medicine, being able to differentiate into cells of the mesenchymal lineages and having extensive proliferative ability. When co-cultured with hepatocytes in two-dimensional cultures, they exert a trophic role, drastically improving hepatocytes survival and functions. In this study we aimed to (i) devise a high throughput system (HTS) to allow testing of a variety of different parameters for cell encapsulation and (ii) using this HTS, investigate whether mesenchymal stromal cells could have beneficial effects on the hepatocytes when co-encapsulated in alginate microbeads. Using our HTS platform, we observed some improvement of hepatocyte behaviour with MSCs, subsequently confirmed in the low throughput analysis of cell function in alginate microbeads. Therefore, our study shows that mesenchymal stromal cells may be a good option to improve the function of hepatocytes microbeads. Furthermore, the platform developed may be used for HTS studies on cell encapsulation, in which several conditions (e.g. number of cells, combinations of cells, alginate modifications) could be easily compared at the same time.